How to write funny add humor to every kind of writing - Kachuba, John B. (Writer's Digest Books, 2001)
Combining classic and original articles with interviews with authors such as Dave Barry, Tom Bodet, and Bill Bryson. This guide teaches writers how to sharpen their sense of humor in their writing.